"Trying to square the circle": Research ethics and Canadian higher education. (January 2020) - Taylor, Alison; Taylor-Neu, Robyn; Butterwick, Shauna
At the European Conference on Educational Research (ECER) in 2016, a panel presented the findings from a survey initiated by the European Educational Research Association Council to examine educational researchers' experiences with the research ethics review process at their universities. Some researchers appeared to be looking to North America for models to govern and regulate university research ethics. In response, our inquiry began from the question: what can European researchers learn from the way ethical review structures and processes have developed in Canada? But as we approached this question, we encountered a more immediate question: to what extent is it possible to address a diversity of research–ethical concerns via a single, bureaucratic policy? Then, how do standardized ethics regimes fail to account for non-standard research—and thereby fail researchers, participants, and communities?; and what is the alternative? In this paper, we explore the history of the development of an ethics regime for Canadian universities, and changes over time. Based on this review, as well as our personal experiences with community-based research, we argue that efforts to regulate the diversity of social sciences research via a uniform policy almost inevitably miss the mark: one ends up trying to "square the circle".